The Impact of Commodities and Digital Assets on Leading Stock Markets: A Study of Cryptocurrency, Gold, and Oil - Mutmainna, Putri; Ria Retnasih, Nora (Universitas Islam Lamongan, 2024)
This research examines the influence of- Cryptocurrencies, Gold Prices, and World Oil Prices on the world's best Composite Stock Index during the 2014-2023 period Purposive sampling approaches were used in conjunction with non-probability strategies to acquire data. Data on cryptocurrencies, gold prices, global oil prices over a ten-year period, and the world's best Composite Stock Index—that is, data on the US, Japan, Germany, England, South Korea, France, Hong Kong, Europe, and Indonesia— are the forms of research data that are available. Panel data regression analysis with the Fixed Effect Model (FEM) was used to evaluate the hypotheses. The study's findings indicate that cryptocurrencies have a favorable impact on the Composite Stock Index, and that a gain in cryptocurrencies indicates an individual's capacity for investing. Rising gold prices are a sign of more people investing in the stock market since gold prices have a favorable impact on the Composite Stock Index. Meanwhile, world oil prices have-a negative effect on the Composite Stock Index because the higher the world-oil-price, the more indirect the income of investors will decrease. Cryptocurrencies, gold prices and world oil simultaneously influence the Composite Stock Index.